How should we treat autopolyploid and parthenogenetic animals taxonomically? - Vogt, Günter (Zootaxa, 2019)
Asexually reproducing and polyploid animals are unresolved problems of taxonomy and nomenclature. The present paper discusses this issue from a theoretical perspective and outlines how the problem was treated in the past. The autotriploid, obligately parthenogenetic marbled crayfish is used as an example to elaborate the conditions under which autopolyploids and parthenogens should be described as separate uniparental species.
Gesehen am 11.03.2020